An evaluation of monitoring of respiratory physiological parameters in patients treated with non-invasive ventilation in the emergency department in Sligo University Hospital in Ireland - Matalasi, Retselisitsoe Vincent (Division of General Surgery, 2022)
Background: Acute respiratory failure is becoming a frequent phenomenon in the emergency department due to increasing life expectancy, and in the last two decades the number of presentations has more than doubled. Non-invasive ventilation has become the treatment modality of choice in selected patients, with a significant reduction of mortality in these cases. However, adequate monitoring of clinical and blood gas parameters is crucial to ensure treatment targets are met. Objective: This study aims to evaluate monitoring of respiratory physiological parameters in patients treated with non-invasive ventilation (NIV) in the ED in Sligo University Hospital. As a secondary objective, the study aims to evaluate how monitoring data influence treatment modification. Methodology: This was a retrospective chart review of 50 patients who presented to the ED in acute respiratory failure and were treated with non-invasive ventilation between September 2017 and March 2019. Results: A total of 50 charts were analysed, 62% female and 38% male. The average age for both genders was 76 years. Results showed that initial and ongoing monitoring of vital signs remained guideline compliant throughout the entire duration of NIV in the ED. All but one patient out of 50 had an initial blood gas analysis done prior to initiation of NIV treatment, while repeat blood gas analysis was inconsistent with 38% (n= 19) who did not have blood gas repeated. Conclusion: The study highlights the discrepancy between monitoring of vital signs and arterial blood gas during treatment of acute respiratory failure patients with non-invasive ventilation in the emergency department. A proforma may help bridge this gap to ensure a standardised care in order to improve treatment outcomes.